“All Kinds of Dirty”: Supermarkets, Markets, and Shifting Cultures of Clean - Moyer, Alexia (Cuizine, 2009)
AbstractThe makers of CLR (the Calcium, Lime, Rust, cleaning product) assure us that there are “all kinds of dirty, one kind of clean.” One can feel confident that soap scum buildup and toilet bowl stains in the bathroom as well as the grease splatters and dried-on tomato sauce in the kitchen can be wiped away with the help of one yellow bottle. The pithy slogan asks us to be preoccupied by dirty in all its forms, without taking into account the many discourses of clean. This article concerns itself with the cult of “cleanness” and the ways in which it has taken hold of the imaginary when it comes to our bodies, the things we put into them, and the spaces we make use of and/or inhabit. I make particular reference here to the spaces in which we buy food, exploring various implications of the staging process enacted in the processing and display of foodstuffs. I set out to examine the ways in which clean is implemented and interpreted by and within two major sites of food shopping: the supermarket and the market.